PEMANASAN GLOBAL DALAM TINJAUAN FILSAFAT YIN-YANG : RELEVANSINYA DENGAN PENGELOLAAN LINGKUNGAN HIDUP DI INDONESIA - , NANDANG SUKARDJO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research entitled Global Warming from the Perspective of Yin Yang Philosophy and Relevancy with Environment Management in Indonesia. Global warming is a problem rooting from human beingâs perception on the nature where they live. A perception orientated to the extremely permissible exploitation of the nature should be followed by the understanding of balance and harmony as the principles of Yin Yang philosophy. The purposes of this study are to describe the meaning of global warming phenomenon, to analyze it in the perspective of Yin Yang philosophy, and to find out the relevancy between Yin Yang philosophy and environment management in Indonesia. The study was a library research. The methodical components used in the data analysis were hermeneutics and heuristics. The formal object was global warming phenomenon. Result of the study indicates as follow: ( 1 ) Global warming is an event or a condition of the increasing average temperature of atmosphere, sea, and land on the globe resulted from human activities and natural processes. Theoretically and analitically, the phenomenon explained the sufficiently serious threat and danger for the survival of life on the globe. ( 2 ) Global warming in the perspective of Yin Yang philosophy was closely related to the concept of harmony as the ontological, epistemological, and axiological concept of the nature of life, natural knowledge, and human methods in making a synergy with its environment. The concept of harmony as the core of Yin Yang philosophy explained that human being in it self has suffered in harmonious condition, so has environment in daily life activities. Such inharmonious condition in relation to the natural laws accured due to the interference of human being, damaging the rules of normality in environmental system. ( 3 ) The concept of harmony in Yin Yang philosophy has an ideological relevance for Indonesia nation. The relevance was between the principle/ concept of harmony as the basis of Yin Yang philosophy and the principle of diversity in the Five Principle. In other words, the concept of harmony also has relevance with futuristic-pragmatic dimensions for Indonesia nation in facing the future by giving attention to the concervation of human resources through the environment management based on the harmonization of human being and nature.